Effect of Grain Boundary on Diffusion of P in Alpha-Fe: A Molecular Dynamics Study - Azeem, M. Mustafa; Wang, Qingyu; Zhang, Yue; Liu, Shengbo; Zubair, Muhammad (Frontiers in Physics, 2019)
In this study, we have investigated the effect of the grain boundary (GB) on the diffusion of a Phosphorus (P) atom in alpha-Fe using molecular dynamics simulations. A Fe-P mixed <110> dumbbell is created in the six symmetric tilt grain boundary (STGB) models. The dumbbells are allowed to migrate at different temperatures from 400 K to 1000 K, with starting positions between 5 Å to 10 Å away from the GB core. The trajectories and mean square displacements (MSD) have been recorded to analyze the diffusion details. The Nudged Elastic Band (NEB) method has been used to study the energy barrier at different positions around the GBs. Our simulation results demonstrate that the GB structure affects the diffusion mechanisms of Fe-P dumbbell. The two low Σ favored GBs display significantly weak trapping effect, which is consistent with the formation energy distribution. The reduction in the migration barrier has been observed due to the decrease of distance from the GB center. Furthermore, the barriers of migration towards the GB are lower than the barriers of migration away from the GB. As evident by NEB calculation, absorption sink effect of GB has been observed. This effect saturates as the distance reaches 8 Å or more. Our simulation results provide an insight into the GB trapping effect in alpha-Fe.